Human Capital Development: Its Implications to Poverty Alleviation (Asia Pacific Journal of Social and Behavioral Sciences, 2012)
This study examined how human capital development relates to poverty alleviation. Specifically, it analyzed trends in basic and tertiary education in consonance with the prevailing poverty incidence in the country, examined whether the human capital production in the poor regions of Luzon, Visayas and Mindanao complemented with the regional development agenda of the local government, and formulated the implications of poverty alleviation to human capital development. Results showed a strong relationship between the drop-out rates in basic education and the poverty incidence in the different regions of the country signifying that poverty mitigation is a crucial element of human development. It was also found that the alignment of regional development frameworks with the program offerings at the tertiary level as well as the LGUs’ provision of job opportunities for college and university graduates are important determinants of poverty alleviation.
Keywords: Human Capital Development, Poverty Alleviation, Education